Is Psychology a Health Profession? An Opinion of a Sample of Psychologists Worldwide - Zych, Izabela; Universidad de Córdoba (2012)
The purpose of the current study is to evaluate the opinions of the scientific community of psychologists on the question if psychology is a health profession. Nowadays, the subject is even more important as there are laws, as for example the Ley de Ordenación de Profesiones Sanitarias (LOPS) [Law for the Organization of the Health Professions] in Spain that should be based on the concept that psychology is or is not a health profession. Moreover, the creation of the common curricula for the whole Europe needs the general agreement and no individual opinion can be valid for these purposes. The present study shows the opinion of 803 scientists who have published at least one article in a clinical or multidisciplinary psychology journal included in the Web of Science, from 42 different countries, 23 major fields of psychology and 32 orientations. The results show that, in general, the participants answered that psychology is a health profession, which is even more evident in case of clinical psychology.